Dynamic Control of the Vortex Pinning Potential in a Superconductor Using Current Injection through Nanoscale Patterns - Kalcheim, Yoav; Katzir, Eran; Zeides, Felix; Katz, Nadav; Paltiel, Yossi; Millo, Oded (Nano letters, 2017)
Control over the vortex potential at the nanoscale in a superconductor is a subject of great interest for both fundamental and technological reasons. Many methods for achieving artificial pinning centers have been demonstrated, for example, with magnetic nanostructures or engineered imperfections, yielding many intriguing effects. However, these pinning mechanisms do not offer dynamic control over the strength of the patterned vortex potential because they involve static nanostructures created in or near the superconductor. Dynamic control has been achieved with scanning probe methods on the single vortex level but these are difficult so scale up. Here, we show that by applying controllable nanopatterned current injection, the superconductor can be locally driven out of equilibrium, creating an artificial vortex potential that can be tuned by the magnitude of the injected current, yielding a unique vortex channeling effect.